Comprehensive support of family caregivers: Are there health system cost offsets?. (4th July 2020) - Van Houtven, Courtney Harold; Smith, Valerie A.; Stechuchak, Karen M.; Berkowitz, Theodore S. Z.; Miller, Katherine E. M.; Shepherd‐Banigan, Megan; Kabat, Margaret; Henius, Jennifer
Abstract: Objectives: To examine the effect of the Department of Veterans Affairs' (VA) Program of Comprehensive Assistance for Caregivers (PCAFC) on total VA health care costs for Veterans. Data Sources: VA claims. Study Design: Using a pre‐post cohort design with nonequivalent control group, we estimated the effect of PCAFC on total VA costs up through 6 years. The treatment group included Veterans ( n  = 32 394) whose caregivers enrolled in PCAFC. The control group included an inverse probability of treatment weighted sample of Veterans whose caregivers were denied PCAFC enrollment ( n  = 38 402). Data Extraction: May 2009‐September 2017. Principal Findings: Total VA costs pre‐PCAFC application date were no different between groups. Veterans in PCAFC were estimated to have $13 227 in VA costs in the first 6 months post‐PCAFC application, compared to $10 806 for controls. Estimated VA costs for both groups decreased in the first 3 years with a narrowing, but persistent and significant, difference, through 5.5 years. No significant difference in VA health care costs existed at 6 years, approximately $10 000 each, though confidence intervals reflect significant uncertainty in cost differences at 6 years. Conclusions: Increased costs arose from increased outpatient costs of participants. Sample composition changes may explain lack of significance in cost differences at 6 years because these costs comprise of early appliers to PCAFC. Examining 10‐year costs could elucidate whether there are long‐term cost offsets from increased engagement in outpatient care.